Formulation of the Model Fluconazole Eye Drop and Its Comparison with the Available Fluconazole Eye Drops - Sunil Thakral; Munish Ahuja (Universitas Padjadjaran, 2012)
The aim of the study was to formulate the model formulation of fluconazole eye drop and then compare it with the available eye drops. The corneal permeation studies were conducted using freshly excised sheep cornea, mounted between donor and receptor. The receptor cell had an internal volume of 11 mL, containing ringer bicarbonate (pH 7.4, 34±1 0C). At appropriated intervals 2 ml. samples were withdrawn from the side arm and were analyzed spectrophotometrically by measuring absorbance at λmax of 260 nm. Each experiment was continued for about 2.0 hrs (triplicate). At the end of the experiment, each cornea (freed from sclera) was weighed, soaked in 1 mL. methanol, dried overnight at 90 °C and reweighed. From the difference in weights corneal hydration was calculated. Even though, the marketed formulation (Zocon) comprised of 0.3% w/v of fluconazole and our model formulation contained only 0.2% w/v of fluconazole, the amount of fluconazole permeated from model formulation and the marketed formulation was respectively 78.34±4.26 and 22.14±1.3. The permeation from model formulation was much greater than other preparations and shows less corneal hydration (80.29±0.47) than others available preparations.Key words: Fungal kerititis, fluconazole, in vitro permeation, corneal hydration, model formulationsFormulasi Tetes Mata Fluconazole dan Perbandingannya dengan Tetes Mata Fluconazole di PasaranAbstrakPenelitian ini bertujuan untuk melakukan formulasi tetes mata flukonazol dan membandingkannya dengan tetes mata yang beredar di pasaran. Studi permeasi kornea dilakukan dengan menggunakan kornea biri-biri yang telah dikeluarkan, disatukan antara donor dan reseptor. Sel reseptor memiliki volume internal 11 mL, mengandung ringer bicarbonate (pH 7,4, 34±1 0C). Sampel diambil pada interval 2 mL sampel dari bagian lengan bejana dan dianalisis menggunakan spektrofotometri dengan pengukuran absorbansi pada λmax 260 nm. Percobaan dilanjutkan selama dua jam (triplikat). Pada akhir percobaan, setiap kornea (dipisahkan dari sklera) ditimbang, direndam dalam metanol, dikeringkan pada suhu 90 C dan ditimbang ulang, perbedaan berat dari hidrasi korena dihitung. Formulasi yang dipasarkan (Zocon) terdiri atas 0,3% w/v flukonazol sedangkan model formulasi dari penelitian ini hanya mengandung 0,2% w/v flukonazol, jumlah flukonazol yang mengalami permeasi dari model formulasi dan formulasi dipasarkan masing-masing sebesar 78,34±4,26 and 22,14±1,3. Permeasi dari model formulasi lebih besar dibandingkan dengan sediaan dan menunjukkan nilai hidrasi korneal lebih kecil (80,29±0,47) dibandingkan dengan sediaan di pasaran.Kata kunci: Fungal kerititis, fluconazole, permeasi in vitro corneal hydration, model formulations